(untitled) (Revista Iberoamericana de Bioética, 2021)
This article rebuilds the dialogue between public health ethics, environmental ethics, and global bioethics by linking the contributions of Jahr, Potter, Leopold and Naess. The first part traces the roots of bioethics and presents the ideas that make this dialogue possible. The second discusses the contributions of Leopold’s land ethics and Naess’s ecosophy to ecological bioethics, and to the One Health approach. Finally, it presents certain dilemmas regarding the resolution of disputes between conflicting value claims on human, animal and environmental health.